Investigation of performance of carbon and glass fibre strengthened concrete beams with different end anchorages - Hiew, Kee Hon (Curtin University, 2012)
In this research, 12 reinforced concrete (RC) beams, comprising two beams as control beams, and 10 beams strengthened with fibre-reinforced polymer (FRP), were tested in a four-point bending configuration to determine the ability of externally bonded composite fabrics to improve the flexural capacity of a beam. The composite fabrics used were made of glass and carbon fibre. The fabrics were bonded to the RC beams using a two-part epoxy. These two fabrics were chosen to allow a variety of fabric strengths to be studied. The external bonded reinforcement (EBR) led to an average 240 per cent increase in flexural capacity. Different end anchorages and application configurations of the externally bonded glass and carbon fibres were evaluated to assess their effectiveness in minimising or preventing the debonding of these externally applied composite materials.The results indicate that the anchorages effectively prevented the debonding of the FRP laminates during flexural testing. Beams that were reinforced with glass fabric but without end anchorages failed, with tensile rupture of the FRP followed by debonding. Beams that were externally bonded with anchorages escaped debonding, instead suffering concrete crushing of the compression zone at mid-span as well as tensile rupture of the composite fabrics. However, the fibre reinforced composite concrete beams exhibited non-ductile failures, which suggests the need for further research to resolve these matters when designing the fibre post-strengthening system.